Revisiting Problem Gamblers’ Harsh Gaze on Casino Services: Applying Complexity Theory to Identify Exceptional Customers - Woodside, Arch; Prentice, C.; Larsen, A. (John Wiley & Sons, 2015)
This study revisits the theory, data, and analysis in Prentice and Woodside (2013). The study here applies fuzzy-set qualitative comparative analysis (fsQCA) to customer service evaluation data from seven mega casinos in the world gambling capital—Macau. The study includes contrarian case analysis and offers complex algorithms of highly favourable customer outcomes—an alternative stance to theory and data analysis in comparison to the dominant logic of statistical analyses that Prentice and Woodside (2013) report. The findings here include more complex, nuanced views on the antecedent conditions relating to high problem-gambling, immediate service evaluations and desired customer behavior measures in casinos. Contrary to the findings using symmetric testing via multiple regression analysis in Prentice and Woodside (2013), this study, using asymmetric testing via fuzzy-set qualitative comparative analysis (fsQCA), recognizes the occurrence of causal asymmetry, and draws conclusions on different algorithms leading to high scores in favorable and unfavorable outcome conditions. The findings indicate that not all problem gamblers gaze on casino services harshly; the minority of problem gamblers who view casinos positively versus harshly may be the most valuable customers for the casinos—the casinos’ exceptional customers.